Arms raised and the making of the gesture: the use of images as a disciplinary mechanism in the MST Braços erguidos e a fabricação do gesto: a imagem como dispositivo disciplinar no interior do MST - Anna Maria Dias Vreeswijk (Discursos Fotográficos, 2009)
This article examines the making of a characteristic gesture of the landless people linked to the Movement of Landless Workers (MST): a raised arm (either with a fist, or holding a machete, an ax or a sickle). It investigates how the MST has used a set of pictures published in the Official Journal of the Landless Rural Workers, owned by the Movement, in order to establish this gesture among the landless people. On that account, this research uses the concept of discipline according to Michel Foucault in his book Discipline in which the author discusses the discipline as a method of control of a particular group of individuals. Este artigo analisa a fabricação de um gesto característico dos sem-terra ligados ao Movimento dos Trabalhadores Rurais Sem Terra (MST): o braço erguido (seja com as mãos cerradas, seja segurando um facão, um machado ou uma foice). Investiga como a direção do MST utilizou um conjunto de imagens publicadas no Jornal dos Trabalhadores Rurais Sem Terra, vinculado ao Movimento, para instituir este gesto entre os sem-terra. Para isso, esta pesquisa utiliza o conceito de disciplina de acordo com Michel Foucault (1987), em seu livro Vigiar e Punir, no qual o autor aborda a disciplina como método de controle de determinado grupo de indivíduos.